Dakwah Digital: Urgensi TikTok sebagai Media Dakwah Bagi Generasi Z: Digital Preaching: The Urgency of TikTok as a Platform for Preaching to Generation Z - Husna, Lathifah Irsyadiyah; Ichsan, Yazida; Amadea, Neysa; Nasekha, Durotun; Purwitasari, Anggie (Dirasat Islamiah: Jurnal Kajian Keislaman, 2023)
The increasingly sophisticated development of technology influences the rapidly developing and dynamic model of da'wah. Digital media is one of the technology trends used among Generation Z today, such as the TikTok application. The purpose of this study is to analyze the urgency of TikTok media as a da'wah medium for Generation Z. This study uses the literature study method. Data sources are obtained from books or research that are relevant to what will be studied. The data obtained are analyzed descriptively, the presentation of the data is described in understandable sentences and then grouped based on the discussion category to obtain conclusions. The results of the study show that TikTok can be an alternative platform for da'wah (preachers). Da'wah through TikTok has implications for the da’i (delivery of da'wah) that is not monotonous or more varied.